The Influence of Bullying Experiences on Mathematics Curiosity in Prospective Mathematics Teachers - Rizka Kamalia Agustin; Rizqona Maharani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
In the current era, bullying is increasingly happening, especially to students. Bullying is an act of hurting other people that can cause mental and psychological trauma. In this case, students need to minimize bullying in order to instill curiosity when learning mathematics. Mathematical curiosity in mathematics learning is a positive attitude that influences the success of achieving mathematics learning goals. This research aims to determine the effect of bullying experiences on students' mathematical curiosity. This research includes correlational research, collecting data through questionnaires to measure variables of bullying experiences and mathematics curiosity. The research sample was taken using cluster random sampling techniques and obtained two classes of students majoring in mathematics totaling 49students. Data analysis in this study used a simple Linear Regression Test. The results of the research show that there is a negative and significant relationship between bullying experiences and mathematical curiosity in prospective mathematics teachers. Curiosity towards mathematics is one of the factors that prevents prospective mathematics teachers from experiencing bullying.